Aplikasi Penerimaan dan Pengeluaran Kas (ARILUKAS) Menggunakan SDLC Waterfall - Ratnawati Ratnawati; Yayu Sri Rahayu (Universitas Multimedia Nusantara, 2021)
Educational institutions are one of the institutions that have a lot of financial transactions in their daily activities, for example new student registration fees, payment of school fees and even grants from the government. Assa'adatul Mahmudiyah, which is our research site, is one of the educational institutions that also has a lot of cash flow transactions. However, problems arise when these transactions are still recorded manually in books or simple spreadsheet files. These problems include rewriting when making reports, calculating and checking funds manually on cash balances and so on. Therefore, making a cash flow application is an alternative to this problem. Data was collected by observing the research site, reference the literature and conducting interviews with the cash manager. While the waterfall method the researchers took as a software development method. With this cash flow application, it can speed up users in making reports and reduce errors when recording cash in and cash out Index Terms— Cash flow application, Cash in and cash out, Waterfall